Those Numerators Look Familiar

Geometry Level 2

1 cos 8 0 3 sin 8 0 = ? \large \frac {1}{\cos 80^\circ } - \frac {\sqrt 3}{\sin 80^\circ } = \ ?

Hint: How can we write the numerators in relation to common trig values?

3 3 3 \sqrt{3} 1 1 0 0 2 2 2 \sqrt{2} 4 4

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Tanishq Varshney
Apr 9, 2015

To get a common denominator, we have sin 8 0 o 3 cos 8 0 o sin 8 0 o cos 8 0 o \large{\frac{\sin 80^{o}-\sqrt{3}\cos80^{o}}{\sin80^{o}\cos80^{o}}} .

Then, we write the numerators in terms of trig values: 2 1 2 sin 8 0 o 3 2 cos 8 0 o sin 8 0 o cos 8 0 o = 2 cos 6 0 o sin 8 0 o sin 6 0 o cos 8 0 o sin 8 0 o cos 8 0 o \large{2 \cdot \frac{\frac{1}{2}\sin80^{o}-\frac{\sqrt{3}}{2}\cos80^{o}}{\sin80^{o}\cos80^{o}}} = \large{2 \cdot \frac{\cos 60^{o}\sin 80^{o}-\sin 60^{o}\cos 80^{o}}{\sin80^{o}\cos80^{o}}}

Using Sine - Sum and Difference Formulas , this is

2 sin ( 8 0 o 6 0 o ) sin 8 0 o cos 8 0 o \large{2 \frac{\sin(80^{o}-60^{o})}{\sin80^{o}\cos80^{o}}}

Using Double Angle Identities , this is

4 sin 2 0 o sin 16 0 o \large{4 \frac{\sin20^{o}}{\sin 160^{o}}}

Using the Fundamental Trigonometric Identity sin ( 18 0 o θ ) = sin ( θ ) \large{\sin(180^{o}-\theta)=\sin(\theta)} , this is

4 sin 2 0 o sin 2 0 o \large{4 \frac{\sin20^{o}}{\sin20^{o}}}

= 4 \huge{=4}

Related: R-method

Shubhrajit Sadhukhan - 1 month, 3 weeks ago
Josh Banister
Apr 10, 2015

Consider the following angle formulas sin 3 x = 3 sin x 4 sin 3 x cos 3 x = 4 cos 3 x 3 cos x \sin{3x} = 3\sin x - 4\sin ^ 3 x \\ \cos{3x} = 4\cos ^ 3 x - 3\cos x If we let x = 8 0 o x = 80^o then sin 8 0 o ( 3 4 sin 2 8 0 o ) = sin 24 0 o = 3 2 cos 8 0 o ( 4 cos 2 8 0 o 3 ) = cos 24 0 o = 1 2 \sin 80^o ( 3 - 4\sin^2 80^o ) = \sin 240^o = -\frac{\sqrt{3}}{2} \\ \cos 80^o ( 4\cos^2 80^o - 3 ) = \cos 240^o = -\frac{1}{2}

Now in reference to the original question. 1 cos 8 0 o 3 sin 8 0 o = 4 cos 2 8 0 o 3 cos 8 0 o ( 4 cos 2 8 0 o 3 ) 3 ( 3 4 sin 2 8 0 o ) sin 8 0 o ( 3 4 sin 2 8 0 o ) = 4 cos 2 8 0 o 3 1 2 + 3 ( 4 sin 2 8 0 o 3 ) 3 2 = 2 ( 4 cos 2 8 0 o 3 + 4 sin 2 8 0 o 3 ) = 2 ( 4 6 ) = 4 \frac{1}{\cos 80^o} - \frac{\sqrt{3}}{\sin 80^o} = \frac{ 4\cos^2 80^o - 3 }{\cos 80^o ( 4\cos^2 80^o - 3 )} - \frac{\sqrt{3}( 3 - 4\sin^2 80^o )}{\sin 80^o ( 3 - 4\sin^2 80^o )} \\ = \frac{ 4\cos^2 80^o - 3 }{-\frac{1}{2}} + \frac{\sqrt{3}( 4\sin^2 80^o - 3 )}{-\frac{\sqrt{3}}{2}} \\ = -2(4\cos^2 80^o - 3 +4\sin^2 80^o - 3) \\ = -2(4 - 6) \\ = \boxed{4}

Moderator note:

Considering that the triple angle formula is a special case of sum and difference formula, it would be simpler to do Tanishq Varshney's way. Either way, it works!

Seems a tad bit unwieldy to do your substitutions.

Sujeeth Jinesh - 6 years, 2 months ago

Log in to reply

The solution still came out right?

Josh Banister - 6 years, 2 months ago

1 cos 8 0 3 sin 8 0 = sin 8 0 3 cos 8 0 cos 8 0 sin 8 0 = 2 ( 1 2 sin 8 0 3 2 cos 8 0 ) 1 2 ( 2 cos 8 0 sin 8 0 ) = 4 ( cos 6 0 sin 8 0 sin 6 0 cos 8 0 ) sin 16 0 = 4 sin ( 8 0 6 0 ) sin ( 18 0 16 0 ) = 4 sin 2 0 sin 2 0 = 4 \begin{aligned} \frac{1}{\cos 80^\circ} - \frac{\sqrt{3}}{\sin 80^\circ} & = \frac{\sin 80^\circ - \sqrt{3}\cos 80^\circ}{\cos 80^\circ \sin 80^\circ} \\ & = \frac{2\left(\frac{1}{2}\sin 80^\circ - \frac{\sqrt{3}}{2}\cos 80^\circ \right)}{\frac{1}{2}\left(2\cos 80^\circ \sin 80^\circ \right)} \\ & = \frac{4(\cos 60^\circ \sin 80^\circ - \sin 60^\circ \cos 80^\circ)}{\sin 160^\circ} \\ & = \frac{4\sin (80^\circ-60^\circ)}{\sin (180^\circ-160^\circ)} \\ & = \frac{4\sin 20^\circ}{\sin 20^\circ} \\ & = \boxed{4} \end{aligned}

I did the same way.

Niranjan Khanderia - 2 years ago

i think this is a much easier way

Wasique Rahaman Gazi - 7 months, 3 weeks ago
Gamal Sultan
Apr 13, 2015

1 = 2 sin 30

square root of 3 = 2 cos 30

cos 80 = sin 10

sin 80 = cos 10

Then the given expression = (2 sin 30 cos 10 - 2 sin 10 cos 30)/sin 10 cos 10 ..... (1)

2 sin 30 cos 10 - 2 sin 10 cos 30 = 2 sin (30 - 10) = 2 sin 20 .......................................... (2)

sin 10 cos 10 = (1/2) sin 20 ........................................................................................................ (3)

From (1) , (2) and (3) we get

Then the given expression = 4

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...